Effects of ascorbic acid immersion of eggs on some hatching properties in quail - Kandemir, Ozge; Kul, Selim (Indian Counc Agricultural Res, 2013)
This study was undertaken to determine the effects of immersion of hatching quail (Coturnix coturnix japonica) eggs into L-ascorbic acid solution on egg white pH, embryonic deaths, and survival of chicks. A total of 5,429 eggs in 9 groups were used. In the first group, immersion into ascorbic acid solution was carried out at the beginning of incubation (BI) (5g/1 min, 5 g/2 min, 10 g/1 min, 10 g/2 min) whereas it was done during incubation (DI) (5g/1 min, 5 g/2 min, 10 g/1 min, 10 g/2 min) in the second group. The third group was used as control group with no treatment. Results indicated that ascorbic acid immersion at BI and DI significantly affected early and middle term embryonic death rates while it was ineffective on late embryonic death rate. pH values measures on day 5 (early term) in BI groups (5g/2 min, 10g/2 min, control) were 8.41, 8.51 and 8.10, respectively, indicating a positive effect of ascorbic acid on egg white pH. Six-week survival of hatched-chicks in BI 10 g/1 min and DI 10g/1 min groups were significantly higher. These results indicated that immersing hatching quail eggs into ascorbic acid solutions may be useful for improving the survival of chicks and for reducing embryonic dead.
Keywords: Ascorbic acid; Embryonic mortality; Japanese quail; pH; Viability